1984
DOI: 10.1128/mcb.4.8.1647
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic turnover of human c-rasH p21 protein of EJ bladder carcinoma and its normal cellular and viral homologs.

Abstract: The EJ bladder carcinoma oncogene is activated by a point mutation in the c-rasH proto-oncogene at the 12th amino acid codon. In an attempt to understand the mechanism of oncogenic activation, a comparative study was undertaken to examine the metabolic turnover and subcellular localization of the p21 protein encoded by the EJ oncogene, the viral oncogene, and its normal cellular homolog. Pulse-labeling experiments indicated that both c-ras p21 proteins were synthesized by a very similar pathway, as was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
0
3

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 19 publications
9
40
0
3
Order By: Relevance
“…There are only very limited published data on the regulation of stability or production/degradation of the Rho proteins. The phosphorylated form of Ras has been shown to be more stable in cells (26), and carboxyl methylation of RhoA and Cdc42 has been reported to increase their half-lives (39). Our results suggest that phosphorylation of Rho proteins in the C-terminal domain could also protect these proteins from degradation.…”
Section: Pkg Activation Increasesmentioning
confidence: 60%
“…There are only very limited published data on the regulation of stability or production/degradation of the Rho proteins. The phosphorylated form of Ras has been shown to be more stable in cells (26), and carboxyl methylation of RhoA and Cdc42 has been reported to increase their half-lives (39). Our results suggest that phosphorylation of Rho proteins in the C-terminal domain could also protect these proteins from degradation.…”
Section: Pkg Activation Increasesmentioning
confidence: 60%
“…Our data (not shown) indicate that all cytosolic Ras constructs had a half-life comparable to that of membranelocalized H-Ras(Q61L) (i.e. Ϸ22 h (20)) and that our results were therefore unlikely to result from variations in protein stability. We also confirmed that all unprenylated Ras proteins remained cytosolic by cell fixation in formaldehyde followed by immunofluorescent staining as described previously (21), using either anti-HA or anti-pan-Ras antibodies visualized with FITC-conjugated secondary antibody on a Zeiss Axioskop fluorescence microscope.…”
Section: Generation Of Cytosolic Gtp-bound Ras Constructs-mentioning
confidence: 68%
“…Our results, however, suggest that production of the p21 ras encoded protein as detected by the monoclonal antibody Y13-259 is not restricted to cells which are actively growing or dividing, either in normal mucosa or in tumours where, although identification of clonogenic tumour stem cells is much less easy, the fact that their growth fraction is only in the region of 15% (Wright, 1984) indicates that the pattern of staining observed cannot be ascribed to them alone. In normal crypts the epithelial cell survival time is of the order of 4-8 days (Wright, 1984) whereas the results of in vitro experiments suggest that the half-life of the c-Ha-ras p21 is only 20 h, (Ulsh & Shih, 1984) although this may not be the case in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…GTP dependent phosphorylation of p21 has been shown to be stimulated by both EGF and insulin (Kamata & Feramisco, 1984). The half-life of the cellular p21 in vitro is of the order of 20h (Ulsh & Shih, 1984). Widespread transcription of ras genes has been documented in embryogenesis (Muller et al, 1983) and increased transcription is seen in regenerating liver (Goyette et al, 1984).…”
mentioning
confidence: 99%